Enigma: Aspects of Multimodal Inter-Semiotic Translation - Cross, Judith Leah (HERMES - Journal of Language and Communication in Business, 2016)
Commercial and creative perspectives are critical when making movies. Deciding how to select and combine elements of stories gleaned from books into multimodal texts results in films whose modes of image, words, sound and movement interact in ways that create new wholes and so, new stories, which are more than the sum of their individual parts. The Imitation Game (2014) claims to be based on a true story recorded in the seminal biography by Andrew Hodges, Alan Turing: The Enigma (1983). The movie, as does its primary source, endeavours to portray the crucial role of Enigma during World War Two, along with the tragic fate of a key individual, Alan Turing. The film, therefore, involves translation of at least two "true" stories, making the film a rich source of data for this paper that addresses aspects of multimodal inter-semiotic translations (MISTs). Carefully selected aspects of tales based on "true stories" are interpreted in films; however, not all interpretations possess the same degree of integrity in relation to their original source text. This paper assumes films, based on stories, are a form of MIST, whose integrity of translation needs to be assessed. The methodology employed uses a case-study approach and a "grid" framework with two key critical thinking (CT) standards: Accuracy and Significance, as well as a scale (from "low" to "high"). This paper offers a stretched and nuanced understanding of inter-semiotic translation by analysing how multimodal strategies are employed by communication interpretants.